Successful treatment of glucocorticoid-resistant acute severe urticaria with JAK1 inhibitor: case report - Wu, Ying; Wang, Long-fei; Yang, He-nian; Kan, Chen-xing; Guo, Xuan; Hao, Guo-dong (Frontiers in Allergy, 2025)
ObjectiveThis study analyzes a case with a JAK1 (Janus Kinase 1) inhibitor was successfully employed to treat a patient with glucocorticoid-resistant acute severe urticaria (ASU), with the aim of improving clinical understanding of this condition.MethodsA retrospective analysis was conducted on the clinical data, diagnosis, treatment, and prognosis of a patient with acute severe urticaria, who was admitted to the Allergy Department of Tangshan Workers’ Hospital on March 10, 2025.ResultsThe patient was a 50-year-old female who presented with widespread skin wheals and itching, along with a sensation of throat obstruction for two days. Upon admission, the patient had a body temperature of 38.5°C. Large, irregularly shaped wheals, up to 10 cm in diameter, were observed on the skin. These wheals were bright red with surrounding erythema and increased upon scratching. Laboratory tests indicated elevated levels of white blood cells (WBC), neutrophils percentage, neutrophils absolute value, total IgE, and interleukin-6 (IL-6). A diagnosis of acute severe urticaria was made. Prior to admission, the patient had been administered with betamethasone sodium phosphate, dexamethasone sodium phosphate, methylprednisolone succinate, diphenhydramine, and calcium gluconate at the emergency department without relief in wheals and itching. Upon admission, the patient was treated with glucocorticoids and JAK1 inhibitors, resulting in the complete regression of the rash and normalization of laboratory indicators.ConclusionThis case suggests that JAK1 inhibitors can achieve satisfactory results in treating glucocorticoid-resistant acute severe urticaria.